Cryptococcal meningitis in a patient with idiopathic CD4+ T lymphopenia - Esquivel Luna, Jeremy Stefan (2021)
Infection with the human immunodeficiency virus (HIV) is the main risk factor for developing cryptococcal meningitis. However, there is a poorly known entity, idiopathic CD4+ T-cell lymphopenia, which leads to an unexplainable CD4+ circulating T-cell deficit, predisposing patients to many complications, including infections caused by opportunistic microorganisms. We present the case of a patient with cryptococcal meningitis secondary to idiopathic T-CD4+ lymphopenia, which, as far as we know, is the very first case of its kind reported in Peru. This entity should be considered in patients negative for HIV infection developing non-common infections of the central nervous system, since outcome, management, and prognosis may be different in patients with this condition.